The genesis of Greek philosophy and science : an outline of the case for revisionist viewpoint - 'Adi Setia Mohd. Dom (International Institute of Islamic Thought and Civilization, IIUM, 1999)
Mainstream academic account of the origins and rise of philosophy and science in Greek civilization emphasises explanations in terms of internal components and causal factors, despite glaring inconsistencies with generally known and accepted facts of Greek intellectual and cultural history. These inconsistencies expose the explanatory inadequacy of the mainstream account, and thus demand an intellectually more satisfying one. In this regard, the purpose of this dissertation is to articulate lucidly an outline of the arguments for the revisionist viewpoint which gives due credit to both internal and external causal factors, and thus draws a much more coherent and plausible picture of the beginnings of rational inquiry in the intellectual adventure of Greek civilization. Specifically, the revisionist viewpoint is articulated within the analytical framework provided by the world system model which serves to suggest the most plausible explanation for the abrupt blossoming of Greek philosophy and science by reference to cultural and intellectual changes brought about through dynamic intercivilizational or transcultural interact10ns over long periods of time Given the archaeological and documentary data of Greek history accepted as such by mainstream and revisionist scholars, the world system model then proceeds to demonstrate its explanatory superiority by the method of inference to the best explanation. By this method, the conclusion reached is that· all things considered, the best explanation of the data is that ancient Egyptian and Levantine learning was initially acquired by the Greeks who then proceeded to preserve and enhance it through their own creative contribution. In other words, the world system model argues that the data point to it and tend to confirm it as a more plausible explanation than the mainstream hellenocentric model. As a scientific hypothesis, the world system model opens new, empirically fruitful avenues of research into uncovering the origins of Greek philosophy and science that should not be overlooked by any interested scholars and students of world intellectual history.